Coefficient of Thermal Diffusivity of Insulation Brick Developed from Sawdust and Clays. (29th December 2014) - Bwayo, E.; Obwoya, S. K.
Abstract : This paper presents an experimental result on the effect of particle size of a mixture of ball clay, kaolin, and sawdust on thermal diffusivity of ceramic bricks. A mixture of dry powders of ball clay, kaolin of the same particle size, and sawdust of different particle sizes was mixed in different proportions and then compacted to high pressures before being fired to 950°C. The thermal diffusivity was then determined by an indirect method involving measurement of thermal conductivity, density, and specific heat capacity. The study reveals that coefficient of thermal diffusivity increases with decrease in particle size of kaolin and ball clay but decreases with increase in particle size of sawdust.